PENGARUH KOMPETENSI, INDEPENDENSI, OBYEKTIVITAS, KOMPLEKSITAS TUGAS, DAN INTEGRITAS AUDITOR TERHADAP KUALITAS HASIL AUDIT - Andy Dwi Cahyono; Andy Fefta Wijaya; Tjahjanulin Domai (REFORMASI, 2015)
This research aims to investigate the influence of competence, independence, objectivity, the complexity of the task, and the integrity of the auditors on the quality of audit results either partially or simultaneously: a case study on Inspectorate of Madiun Regency, East Java. Data collection techniques used were questionnaires, observations, and interviews. The population is around the auditor Inspectorate active in carrying out the audit task, as many as 22 auditors. The dependent variable (Y) is used in the Quality Audit Result at Inspectorate of Madiun Regency, while the independent variable is the competence of auditors (X1), the independence of auditors (X2), the objectivity of the auditor (X3), the complexity of the task of auditors (X4), and the integrity of the auditors (X5). This research provides results that competence, independence, objectivity, the complexity of the task, and the integrity of auditors simultaneously gives significant effect on the quality of audit results. Auditor competence positively affect the quality of audit results. The more competent an auditor then the more qualified the results of the examination. Auditor independence positively affect the quality of the results of the examination. The higher level of independence of the auditor, the more qualified the examination results. Auditor’s objectivity positively affect the quality of the results of the examination. The more objective an auditor then the more qualified the results of the examination. Complexity task of auditor adversely affect the quality of the results of the examination. The more complex the task of an auditor then decreasing the quality of the examination. Integrity auditors positively affect the quality of the results of the examination. The higher the integrity of an auditor then the more qualified the results of the examination.